Composite cathodes for protonic ceramic fuel cells: Rationales and materials. (1st June 2022) - Wang, Meng; Su, Chao; Zhu, Zhonghua; Wang, Hao; Ge, Lei
Abstract: Protonic ceramic fuel cells (PCFCs) or proton-conducting solid oxide fuel cells (SOFCs) are a class of electrochemical devices with high proton conductivity at the intermediate, even low operating temperatures (450–750 °C), which directly convert the chemical energy of hydrogen or hydrogen-containing fuels into electricity in a clean and efficient manner. In comparison to oxygen-ion conducting SOFCs, the operation at lower operating temperature overcomes the incompatibility and cathode delamination issues in high-temperature operated SOFCs. More attractively, the fuel is not diluted owing to the production of water at the cathode side. However, lowing working temperature weakens the electrode reaction kinetics and the ion migration, therefore the rational design of high-performance cathode materials is highly desired for PCFCs. Herein, we provide a review on the design criteria and state-of-art materials of PCFC composite cathodes including proton-conducting composite, proton-blocking composite and other types of composite cathodes, and discuss the underlying rationales and mechanisms. In particular, we discuss the feasibility of self-assembled composite cathodes used in PCFCs, and point out the future development directions of composite cathodes.